1993
DOI: 10.1002/hed.2880150310
|View full text |Cite
|
Sign up to set email alerts
|

Tumor markers in the diagnosis and follow‐up of head and neck cancer: Role of CEA, CA 19‐9, SCC, TK, and dttpase

Abstract: The clinical relevance of the carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9, squamous cell carcinoma antigen (SCC), thymidine kinase (TK), and deoxythymidine-5'-triphosphatase (dTTPase) as tumor markers in the diagnosis and follow-up treatment of 26 patients with head and neck cancer is evaluated. Serum levels prior to treatment were found elevated just above the upper limit of normal in 46% (SCC), 15% (CEA), 12% (CA 19-9), 27% (TK), and 39% (dTTPase) of all patients. If all markers were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…An analysis of serum concentrations of multiple biological markers, including basic fibroblast growth factor, vascular endothelial growth factor, and matrix metalloproteinase-2 by ELISA in 26 HNSCC patients after primary chemoradiation therapy, showed that only increased basic fibroblast growth factor concentrations correlated with earlier loss of locoregional control (18). Other studies have investigated several conventional serological markers in 26 HNSCC patients and found none to be of statistical significance (19). Antibodies to p53 tumor suppressor protein were detected in the sera of 25% of 271 patients with oral SCC (20) and at a low percentage in saliva from HNSCC patients (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of serum concentrations of multiple biological markers, including basic fibroblast growth factor, vascular endothelial growth factor, and matrix metalloproteinase-2 by ELISA in 26 HNSCC patients after primary chemoradiation therapy, showed that only increased basic fibroblast growth factor concentrations correlated with earlier loss of locoregional control (18). Other studies have investigated several conventional serological markers in 26 HNSCC patients and found none to be of statistical significance (19). Antibodies to p53 tumor suppressor protein were detected in the sera of 25% of 271 patients with oral SCC (20) and at a low percentage in saliva from HNSCC patients (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing the titles and abstracts of the 493 studies, 478 were excluded: 40 due to repetition, 190 recruited patients in whom TK1 was detected following chemotherapy or surgery, the full text was unavailable for 50 studies and 198 studies were not conducted on human subjects. A total of 15 eligible studies involving 1,840 patients and 1,664 controls were included in the pooled analyses (12,19,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1). Among these, 12 investigated solid tumors (8,12,(32)(33)(34)(35)(36)(37)(38)(39)(40)42,44) and included 1,538 patients and 1,484 controls and 3 investigated non-solid tumors (19,40,42) and included 302 patients and 180 controls. The solid tumors included 7 breast carcinomas (33,35-39,43), 2 renal Funnel plot of sensitivity and specificity of thymidine kinase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 La región cromosómica 11q13 es un lugar crítico para la traslocación de los oncogenes bcl-1, PRAD-1/ciclina D1 y el gen del factor de crecimiento del fibroblasto HST1. La amplificación entre 2 y 10 veces del locus 11q13 se correlaciona con un patrón de infiltración más difuso del tumor y peor grado de diferenciación pero sin implicación pronóstica.…”
unclassified